(NmETEORY I METEORNOE WE]ESTWO (B/s - (NwOLO]UK(B, (N`RIJ iWANOWI^s; (NkA]EEW(B, (NbORIS lEONIDOWI^s; (NkRU^INENKO(B, (NwITALIJ gRIGORXEWI^s ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 281-291 (291 (NNAZW(B.)s
(NrEZ(B.: (NANGL(B.s
(Nan ussr(B, (NgL(B. (NASTRON(B. (NOBSERWATORIQs
Keywords: (NmETEORYs